Induction chemotherapy followed by surgery for advanced oesophageal cancer. Issue 3 (March 2015) - Toxopeus, E.L.A.; Talman, S.; van der Gaast, A.; Spaander, V.M.C.W.; van Rij, C.M.; Krak, N.C.; Biermann, K.; Tilanus, H.W.; Mathijssen, R.H.J.; van Lanschot, J.J.B.; Wijnhoven, B.P.L.
Abstract Background Patients with locoregionally advanced oesophageal tumours or disputable distant metastases are referred for induction chemotherapy with the aim to downstage the tumour before an oesophagectomy is considered. Study design Patients who underwent induction chemotherapy between January 2005 and December 2012 were identified from an institutional database. Treatment plan was discussed in the multidisciplinary team. Response to chemotherapy was assessed by CT. Survival was calculated using the Kaplan Meier method. Uni- and multivariable analyses were performed to identify prognostic factors for survival. Results In total 124 patients received induction chemotherapy mainly for locoregionally advanced disease (n = 80). Surgery was withheld in 35 patients because of progressive disease (n = 16) and persistent unresectability (n = 19). The median overall survival of this group was 13 months (IQR: 8–19). The remaining 89 patients underwent surgery of which 13 still had unresectable tumour or distant metastases. Of the 76 patients that underwent an oesophagectomy, 50 patients had tumour free resection margins (66%) with an estimated 5-year survival of 37%. A positive resection margin (HR 4.148, 95% CI 2.298–7.488, p < 0.0001) was associated with a worse survival in univariable analysis, but only pathological lymph node status with increasing hazard ratio's (6.283–10.283, p = 0.001) remained significant after multivariable analysis. Conclusion Induction chemotherapy downstages the tumour and facilitates a radical oesophagectomy in patients with advanced oesophageal cancer. Pathological lymph node status is an independent prognostic factor for overall survival.